2014
DOI: 10.5154/r.rchscfa.2013.09.038
|View full text |Cite
|
Sign up to set email alerts
|

FERTILIZACIÓN CON BORO EN PLANTACIONES DE Eucalyptus urophylla S. T. Blake en TABASCO

Abstract: RESUMENE l presente trabajo se realizó en plantaciones comerciales de Eucalyptus urophylla de la empresa Forestaciones Operativas de México, S. A. de C. V. (FOMEX) en Huimanguillo, Tabasco, Méxi-co, con la finalidad de conocer el efecto de la adición de boro (B) sobre el crecimiento de dicha especie. Se dio seguimiento a 199 árboles de E. urophylla que recibieron diferentes dosis de B (0, 6 y 12 g·árbol -1 ) durante el establecimiento. El diámetro y la altura de los árboles se midieron a las edades de 1.5, 4.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
(34 reference statements)
1
1
0
1
Order By: Relevance
“…Comparing the results with critical values indicated by Bennet, 27 the absorption of macronutrients showed similar concentrations as those reported by Bonomelli and Suarez 28 . The concentration of microelements, such as boron (B), should also be considered, for example, research has shown the critical role of B in the plant cell walls as a meeting microelement in forest plantations, which can result in poor growth 29 . As described in Guo et al ., 24 in litterfall and nutrient return, a 3‐year rotation for three Eucalyptus species, was highly dependent on the degree of biomass production and nutrient uptake.…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…Comparing the results with critical values indicated by Bennet, 27 the absorption of macronutrients showed similar concentrations as those reported by Bonomelli and Suarez 28 . The concentration of microelements, such as boron (B), should also be considered, for example, research has shown the critical role of B in the plant cell walls as a meeting microelement in forest plantations, which can result in poor growth 29 . As described in Guo et al ., 24 in litterfall and nutrient return, a 3‐year rotation for three Eucalyptus species, was highly dependent on the degree of biomass production and nutrient uptake.…”
Section: Resultssupporting
confidence: 74%
“…28 The concentration of microelements, such as boron (B), should also be considered, for example, research has shown the critical role of B in the plant cell walls as a meeting microelement in forest plantations, which can result in poor growth. 29 As described in Guo et al, 24 in litterfall and nutrient return, a 3-year rotation for three Eucalyptus species, was highly dependent on the degree of biomass production and nutrient uptake. Over this period, 20% of the total above-ground biomass produced was in the form of litter, and via the litterfall, up to 24% of the total N uptake was returned to the soil surface.…”
Section: Nutritional Storage Soilmentioning
confidence: 78%
“…Análisis de varianza para el incremento del diámetro a la base en el experimento de fertilización en brinzales de Juniperus deppeana Steud. -Juárez, et. al, 2014).…”
Section: Incremento En El Diámetro a La Baseunclassified